TAZ Induces Migration of Microglia and Promotes Neurological Recovery After Spinal Cord Injury - Hu, Xuyang; Huang, Jinxin; Li, Yiteng; Dong, Lei; Chen, Yihao; Ouyang, Fangru; Li, Jianjian; Li, Ziyu; Jing, Juehua; Cheng, Li (Frontiers in Pharmacology, 2022)
Following spinal cord injury (SCI), microglia gradually migrate to the edge of the lesion, interweaving around the border of the lesion to form the microglial scar, which performs inflammatory limiting and neuroprotective functions. Recent reports showed that Yes-associated protein (YAP) was expressed in astrocytes and promoted the formation of astrocytic scars, while YAP was not expressed in microglia after SCI. YAP and its paralogue transcriptional coactivator with PDZ-binding motif (TAZ) are transcriptional coactivators, which have a similar functional role as both are negatively regulated by the Hippo signalling pathway. However, the expression and function of TAZ after SCI are unclear. Our research group previously found that Fascin-1 was highly expressed in microglia and promoted migration of microglia after SCI, and that, there was a close regulatory relationship between Fascin-1 and YAP/TAZ. In this study, we demonstrated that TAZ was significantly upregulated and mainly expressed in microglia after SCI, and accumulated in the nuclei of microglia in the spinal cord at 14 days post-SCI. Moreover, TAZ was upregulated and accumulated in the nuclei of anti-inflammatory M2-like (M2-L) polarized or myelin-treated microglia. Additionally, XMU-MP-1 (an inhibitor of the Hippo kinase MST1/2 to active TAZ) promoted the aggregation of microglia around the lesion core, resulting in the formation of microglial scars and the functional recovery of mice after SCI. Our findings also indicated that TAZ promoted microglial migration in vitro. Mechanistically, Fascin-1 interacted with TAZ, which upregulated TAZ expression and induced TAZ nuclear accumulation in microglia to promote microglial migration. These findings revealed that TAZ mediated microglial migration to the edge of the lesion core, promoting the formation of microglial scars and functional recovery after SCI. Moreover, TAZ was downstream of Fascin-1, which positively regulated microglial migration after SCI.